AtHB40 modulates primary root length and gravitropic response involving CYCLINB and auxin transporters. - Mora, Catia C; Perotti, María Florencia; González-Gandío, Eduardo; Ribone, Pamela Anahí; Cubas, Pilar; Chan, Raquel Lía (Elsevier, 2022)
Gravitropism is a finely regulated tropistic response based on the plant perception of directional cues. Such perception allows them to direct shoot growth upwards, above ground, and root growth downwards, into the soil, anchoring the plant to acquire water and nutrients. Gravity sensing occurs in specialized cells and depends on auxin distribution, regulated by influx/efflux carriers. Here we report that AtHB40, encoding a transcription factor of the homeodomain-leucine zipper I family, was expressed in the columella and the root tip. Athb40 mutants exhibited longer primary roots. Enhanced primary root elongation was in agreement with a higher number of cells in the transition zone and the induction of CYCLINB transcript levels. Moreover, athb40 mutants and AtHB40 overexpressors displayed enhanced and delayed gravitropistic responses, respectively. These phenotypes were associated with altered auxin distribution and deregulated expression of the auxin transporters LAX2, LAX3, and PIN2. Accordingly, lax2 and lax3 mutants also showed an altered gravitropistic response, and LAX3 was identified as a direct target of AtHB40. Furthermore, AtHB40 is induced by AtHB53 when the latter is upregulated by auxin. Altogether, these results indicate that AtHB40 modulates cell division and auxin distribution in the root tip thus altering primary root length and gravitropism.
Keywords: Raíces (Botánica); AtHB40; HD-Zip; LAX2; LAX3; PIN2; CYCLINB1.1; Gravitropism; Root development